English for everyday activities - J.Zwier, Lawrence (Trẻ, 2009)
TTS ghi: The most pratical illustrated self - study&Course book for English learners; Gồm những chủ đề, tình huống thường gặp hàng ngày, giúp người học học hỏi những kỹ năng cần để giao tiếp.